2016
DOI: 10.1515/raon-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of severe infections in afebrile neutropenic cancer patients

Abstract: BackgroundIn some neutropenic cancer patients fever may be absent despite microbiologically and/or clinically confirmed infection. We hypothesized that afebrile neutropenic cancer patients with severe infections have worse outcome as compared to cancer patients with febrile neutropenia.Patients and methodsWe retrospectively analyzed all adult cancer patients with chemotherapy-induced neutropenia and severe infection, who were admitted to the Intensive Care Unit at our cancer center between 2000 and 2011. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 45 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…There was a relatively high prevalence of respiratory pathogens and high incidence of ARI. The univariate analysis conducted indicated that, the presence of a pathogen correlated well with at least one of the ARI-like symptoms which is similar to other studies from different countries [ 3 , 24 , 28 , 29 ]. Additionally, the high prevalence (61%) of bacteria in this study confirms the findings of Margolis and colleagues [ 30 ] which suggests that, these pathogens interact with one another in a common niche, hence may co-colonize.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…There was a relatively high prevalence of respiratory pathogens and high incidence of ARI. The univariate analysis conducted indicated that, the presence of a pathogen correlated well with at least one of the ARI-like symptoms which is similar to other studies from different countries [ 3 , 24 , 28 , 29 ]. Additionally, the high prevalence (61%) of bacteria in this study confirms the findings of Margolis and colleagues [ 30 ] which suggests that, these pathogens interact with one another in a common niche, hence may co-colonize.…”
Section: Discussionsupporting
confidence: 86%
“…and Strojnik et al . also demonstrated that fever may be absent in some cancer patients regardless of microbiologically and/or clinically confirmed infections [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 The most common outcome of chemotherapeutic agents is neutropenia that could lead to the severity of bacterial infections in patients suffering from cancer. 2 Correspondence: Morteza Saki; Sakineh Seyed-Mohammadi Tel +98 9364221187; +98 9352655807 Fax +98 6133332036 Email mortezasaki1981@gmail.com; sakinehseyedmohammadi@gmail.com…”
Section: Introductionmentioning
confidence: 99%
“…For example, FN patients can present acutely but insidiously where fever is the only manifestation of severe underlying infection (Kao et al, 2018). Previous studies also identified that one-third of neutropenic patients could be afebrile when presenting to the ED but had significantly higher 30 day in-hospital mortality rates than FN patients (Freifeld et al, 2011;Strojnik et al, 2016). Therefore, this harmful emergency can go unnoticed despite the illness's severity and deteriorates to sepsis and septic shock.…”
Section: Research Articlementioning
confidence: 99%